2012
DOI: 10.5194/tc-6-613-2012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of permafrost dynamics in Alaska using a high spatial resolution dataset

Abstract: Abstract. Climate projections for the 21st century indicate that there could be a pronounced warming and permafrost degradation in the Arctic and sub-Arctic regions. Climate warming is likely to cause permafrost thawing with subsequent effects on surface albedo, hydrology, soil organic matter storage and greenhouse gas emissions.To assess possible changes in the permafrost thermal state and active layer thickness, we implemented the GIPL2-MPI transient numerical model for the entire Alaska permafrost domain. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
154
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(160 citation statements)
references
References 35 publications
5
154
1
Order By: Relevance
“…The effect of the SOL has been well presented in several modeling studies. For example, Lawrence and Slater (2008) showed that soil organic matter affects the permafrost thermal state in the Community Land Model, and Jafarov et al (2012) discussed the effect of the SOL in the regional modeling study for Alaska, United States. Recently, Chadburn et al (2015a, b) incorporated an SOL in the Joint UK Land Environment Simulator (JULES) model to illustrate its influence on ALT and ground temperatures both at a site-specific study in Siberia, Russia, and globally.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the SOL has been well presented in several modeling studies. For example, Lawrence and Slater (2008) showed that soil organic matter affects the permafrost thermal state in the Community Land Model, and Jafarov et al (2012) discussed the effect of the SOL in the regional modeling study for Alaska, United States. Recently, Chadburn et al (2015a, b) incorporated an SOL in the Joint UK Land Environment Simulator (JULES) model to illustrate its influence on ALT and ground temperatures both at a site-specific study in Siberia, Russia, and globally.…”
Section: Introductionmentioning
confidence: 99%
“…Jafarov et al (2012) and Westermann et al (2013) produced a transient run of the ground thermal state in Alaska to assess permafrost dynamics under IPCC change scenarios. Another meso-scale modelling effort, that of Gisnå s et al (2013), provides an equilibrium model of permafrost distribution in Norway at a spatial resolution of 1 km 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The probability of permafrost occurrence and most likely permafrost conditions are determined by computing the 16 indices. Although PIC quantitatively integrates most of these indices based on previous studies (Jafarov et al, 2012;Nelson et al, 1997;Riseborough 15 et al, 2008;Smith and Riseborough, 2010;Zhang et al, 2005;Zhang et al, 2014), it still has several limitations.…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…Permafrost is a subsurface feature that is difficult to directly observe and map. These methods integrate the effects of air and ground temperatures, topography, vegetation, and soil properties to map permafrost spatially and explicitly (Gisnå s et al, 2013;Jafarov et al, 2012;Zhang et al, 2014). Weather observation data, including air and soil temperatures with different depths, are the 15 main inputs for single-point simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation